The Impact of CSR Disclosure on Firm Financial Performance: The Mediating Role of Competitive Advantage in Indonesia's Manufacturing Sector - Dewa Krisdianto; Berto Usman (STIE Indonesia Banking School, 2025)
This study examines the effect of Corporate Social Responsibility Disclosure (CSRD) on the financial performance of manufacturing companies in Indonesia, with competitive advantage as a mediating variable. The background of this research lies in the increasing importance of CSR as a strategic tool to enhance corporate value and sustainability in a highly competitive business environment. A quantitative approach with panel data regression was applied to 285 firm-year observations of companies listed on the Indonesia Stock Exchange from 2019 to 2023. Financial performance was measured using Return on Assets (ROA), Return on Equity (ROE), and Earnings per Share (EPS), while CSRD was assessed based on the Global Reporting Initiative (GRI) guidelines. Competitive advantage was measured through reputation and innovation. Data analysis was performed using Stata MP 17 to ensure efficient processing of large-scale panel data. The results show that CSRD has a consistently positive effect on all indicators of financial performance. However, the mediating role of competitive advantage reveals a negative direction, indicating that the benefits of CSR have not been fully converted into short-term financial gains. These findings reinforce the relevance of the Resource-Based View (RBV) in developing countries and emphasize the importance of managing CSR strategically to create sustainable competitive advantages.